2016
DOI: 10.1080/01676830.2016.1193547
|View full text |Cite
|
Sign up to set email alerts
|

Review on surgical management of ptosis and the use of phenylephrine: A national survey of British Oculoplastic Surgery Society (BOPSS) UK Consultants

Abstract: We assess current practice using topical phenylephrine by British Oculoplastic Surgery Society (BOPSS) consultants in the surgical management of ptosis. All UK consultant BOPSS members were invited to participate in a web-based survey, consisting of 8 questions relating to the surgical management of adult primary involutional ptosis with normal levator function and the use of phenylephrine in the management of ptosis. 53 BOPSS consultants (43%) completed the survey, of which 76% perform anterior approach levat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Finally, only 5% phenylephrine eye drops are commercially available in Japan, although 2.5% phenylephrine eye drops are commonly used in other countries. 25,26 A previous study showed more cardiovascular adverse effects after 10% phenylephrine instillation, compared with 2.5% phenylephrine instillation. 27,28 Although we used 5% phenylephrine eye drops, this may cause a greater risk of adverse side effects than 2.5% phenylephrine instillation.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, only 5% phenylephrine eye drops are commercially available in Japan, although 2.5% phenylephrine eye drops are commonly used in other countries. 25,26 A previous study showed more cardiovascular adverse effects after 10% phenylephrine instillation, compared with 2.5% phenylephrine instillation. 27,28 Although we used 5% phenylephrine eye drops, this may cause a greater risk of adverse side effects than 2.5% phenylephrine instillation.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, α 1adrenoceptor agonists such as phenylephrine, are components of oral over-the-counter medications to alleviate the congestive symptoms of the common cold and influenza. In addition, the imidazolines, oxymetazoline and naphazoline, are common components of topical nasal decongestants, mydriatic eye drops, and more recently dermatological formulations for the treatment of facial erythema in rosacea (Kircik et al, 2018;Mota & Norris, 2016;Vaidyanathan, Williamson, Clearie, Khan, & Lipworth, 2010). Interestingly, oxymetazoline and naphazoline are low efficacy agonists with reasonable selectivity for α 1Aadrenoceptors (10-to 30-fold; Akinaga et al, 2013;Minneman, Theroux, Hollinger, Han, & Esbenshade, 1994), further supporting the relevance of this subtype in vasoconstriction.…”
Section: α 1 -Adrenoceptors In Arteriesmentioning
confidence: 99%
“…In the United Kingdom, 77% of surgeons use phenylephrine testing to demonstrate an idea of surgical outcome to the patient, whereas 62% use it to detect subclinical contralateral ptosis …”
Section: Phenylephrine Testing—does It Matter?mentioning
confidence: 99%
“…50 In the United Kingdom, 77% of surgeons use phenylephrine testing to demonstrate an idea of surgical outcome to the patient, whereas 62% use it to detect subclinical contralateral ptosis. 51 About 65% of surgeons used phenylephrine testing to determine their surgical approach, utilizing a posterior approach for >2 mm lid elevation with phenylephrine testing and an anterior approach for <2 mm lid elevation. 51 But is this importance attributed to phenylephrine testing justified?…”
Section: Phenylephrine Testing-does It Matter?mentioning
confidence: 99%
See 1 more Smart Citation